EFEKTIVITAS PEMBERIAN MINYAK ZAITUN TERHADAP KEJADIAN STRIAE GRAVIDARUM PADA IBU HAMIL PRIMIGRAVIDA TRIMESTER III DI WILAYAH KERJA PUSKESMAS PALAPA KOTA BANDAR LAMPUNG TAHUN 2018 - Maternity, Dainty (Jurnal Ilmiah Bidan (JIB), 2021)
ABSTRACT Women during pregnancy need time to adapt to various changes. Changes in the skin, namely the skin surface is very stretched which causes collagen fibers to rupture called striae gravidarum (SG). Changes that occur in the third trimester of pregnant women include frequent urination 50%, striae gravidarum 50%, hemorrhoids 60%, shortness of breath 60% and back pain 70%. This study aims to determine the effectiveness of olive oil on the incidence of striae gravidarum in primigravida trimester III pregnant in the Palapa Health Center in Bandar Lampung 2018. The type of research used in this study is quantitative. The research design uses an experimental method of quasi-experimental approach with a pretest-posttest design with control group. The population study is all primigravida pregnant in the third trimester of pregnancy with a sample of 40 samples (20 experiments and 20 controls) with the sampling technique using purposive sampling. Statistical test uses t-independent test . The results of the study, it was found that the mean score of the striae gravidarum pretest of olive oil was experimental group 4.50, and the standard deviation was 1,573, the mean pretest of the control group was 2.54 and the deviation was 0.887. the mean score of the striae gravidarum postest olive oil experimental group 1.30 and the standard deviation 0.571, the mean in the control group 2.35 with a standard deviation of 0.678. There is an effect of olive oil on the incidence of striae gravidarum in the experimental group (p-value = 0.000). There was no effect of olive oil on the incidence of striae gravidarum in the control group (p-value = 0.163). It is expected for pregnant to use olive oil since the beginning of pregnancy to prevent striae gravidarum on the skin. Keywords: Pregnant, Striae Gravidarum, Olive Oil